Temporal nutrient release pattern of coal-mine affected agricultural soil under different amelioration practices - Saikia, Prerna; Naorem Janaki Singh (Umiam : CPGSAS, CAU(Imphal), 2024)
The Jaintia Hills district in Meghalaya, India, is rich in natural plant life and mineral resources, but extensive coal mining has severely damaged local ecosystems. In Latyrke village, East Jaintia Hills, potential agricultural soils near the coal-affected areas suffer from low productivity due to unscientific mining practices leading to acid mine drainage. This results in low pH, high sulphur, increased exchangeable Al3+, elevated heavy metals (Fe, Mn, Cu), and reduced availability of phosphorus, potassium, and zinc. This study focuses on the impacts of these mining activities on agriculture, targeting agricultural crop fields in Latyrke, Saipung block. The soil samples collected from 30 different sites showed a range of physico-chemical properties, with pH values between 4.53 and 4.81 and electrical conductivity (EC) ranging from 0.13 to 0.16 dS mp-1(B. Nutrient analysis revealed low fertility, with available nitrogen(N) between 219.67 kg hap-1 (Band 307.87 kg hap-1(B, phosphorus(P) from 9.78 kg hap-1 (Bto 21.14 kg hap-1(B, and potassium(K) between 104.23 kg hap-1 (Band 238.32 kg hap-1(B. Organic carbon (OC) content varied between 1.66% to 2.48%. Micronutrient analysis revealed very high levels of iron (37.24 to 70.14 mg kg-1), high manganese (7.12 to 10.34 mg kg-1), sufficient copper (0.41 to 0.61 mg kg-1), and deficient zinc concentrations (0.43 to 0.55 mg kg-1). The bulk density ranged from 0.86 g cmp-3 (Bto 1.29 g cmp-3(B, with soil textures identified as sandy clay loam, sandy loam, and clay loam. Soil colors varied from yellowish brown to dark greyish-brown. The worst affected sites among these 30 sites were selected for amelioration. To ameliorate the soil, agricultural lime and cement kiln dust were tested. The effectiveness of these treatments was assessed through an incubation study, measuring temporal nutrient release patterns and changes in soil properties over 100 days. The study aims to identify optimal amelioration strategies to restore soil fertility and enhance agricultural productivity in coal-mine-affected areas.The study was carried out with two main objectives: (i) To study the effect of acid mine drainage on phosphorus fixation and (ii) To study the nutrient release pattern under different amelioration practices. Treatments included the application of Cement Kiln Dust (CKD) and Agricultural lime (Ag. Lime) based on their effective neutralizing value (ENV). A total of 9 treatments, four involving Ag. Lime (100%,75%,50% and 25% lime requirement based on ENV of Ag. Lime), four involving CKD (100%,75%,50% and 25% lime requirement based on ENV of CKD) and one control was formulated. The results showed that the phosphorus fixation capacity reduced from around 86.00%-93.00%(initial) to approximately 65.00% - 66.57% (60 DOI) on addition of various graded doses of phosphorus. Over a 100-day incubation period, CKD consistently elevated soil pH more effectively than agricultural lime, reaching up to 6.29. Soil available nitrogen increased from 219.67 kg ha-1 to 260.00 kg ha-1, with the highest levels observed in CKDtreated soils. Available phosphorus rose from 9.78 kg ha-1 to 18.75 kg ha-1, while available potassium increased from 104.23 kg ha-1 to 137.99 kg ha-1, both showing significant improvement with CKD and lime treatments. Soil organic carbon declined from 1.66% to 1.24%, and electrical conductivity fluctuated between 0.15 and 1.03 dS m-1. CKD treatment(T2) also enhanced sulphur availability to 45.00 kg ha-1 at 60 DOI and decreased DTPA-Fe from 70.14 to 48.70 kg ha-1. In terms of N,P,K release pattern, almost all the treatments were seen to follow quadratic functions except control following a linear function in terms of nitrogen release.. Treatment T2 (100% LR based on ENV of CKD) significantly increased soil pH, EC, available N,P,K and S while decreasing DTPA-Fe,SOC and phosphorus fixing capacity of soil. Since, T2 outperformed all the treatments in improving the pH and overall nutrient status of the soil, 100% LR based on ENV of CKD can be considered to be the best treatment for ameliorating the soil acidity and its adverse effects in the coalmine affected agricultural lands.s
Includes bibliographical references.
Keywords: Soil conditions; Cement kiln dust; Agricultural lime; Phosphorus fixation; Unscientific coal mining